2018
DOI: 10.3390/medicines5030075
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Raw, Natural Medical Cannabis Flower for Treating Insomnia under Naturalistic Conditions

Abstract: Background: We use a mobile software application (app) to measure for the first time, which fundamental characteristics of raw, natural medical Cannabis flower are associated with changes in perceived insomnia under naturalistic conditions. Methods: Four hundred and nine people with a specified condition of insomnia completed 1056 medical cannabis administration sessions using the Releaf AppTM educational software during which they recorded real-time ratings of self-perceived insomnia severity levels prior to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 37 publications
(50 reference statements)
1
15
0
6
Order By: Relevance
“…Only sessions with baseline symptom intensity levels exceeding zero were included in order to allow for the existence of a treatment effect. We further restricted our sample to symptom levels reported within 4 h postcannabis consumption, similar to previous investigations (Cuttler et al 2018;Vigil et al 2018). In other words, we included only sessions with at least one post-cannabis symptom level reported within 4 h. A total of 23,055 cannabis administration sessions, recorded by 4127 individuals, reported a baseline symptom intensity of one or greater for at least one cannabis administration session used to treat anxiety, agitation/irritability, or stress.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only sessions with baseline symptom intensity levels exceeding zero were included in order to allow for the existence of a treatment effect. We further restricted our sample to symptom levels reported within 4 h postcannabis consumption, similar to previous investigations (Cuttler et al 2018;Vigil et al 2018). In other words, we included only sessions with at least one post-cannabis symptom level reported within 4 h. A total of 23,055 cannabis administration sessions, recorded by 4127 individuals, reported a baseline symptom intensity of one or greater for at least one cannabis administration session used to treat anxiety, agitation/irritability, or stress.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to including product characteristics, we also controlled for session-level pre-cannabis use symptom intensity and session length (minutes up to 4 h—symptom updates beyond 4 h are not included in our analysis). Baseline symptom intensity is included in all regressions because higher starting symptom levels are associated with greater symptom relief (Vigil et al 2018 ). Session length (time from start until the last symptom was reported within 4 h) is included because the effects of inhaled cannabis may vary systematically with session length.…”
Section: Methodsmentioning
confidence: 99%
“…CBD (primarily nabiximols) may improve short-term sleep outcomes in patients with SDs secondary to obstructive sleep apnoea, fibromyalgia, chronic pain, or multiple sclerosis (National Academies of Sciences, Engineering, and Medicine, 2017). The anecdotal use of cannabis derivatives for insomnia and parasomnia is largely widespread (Chagas et al, 2014;Vigil et al, 2018). Naturalistic data on adult patients showed a major subjective relief from insomnia with CBD but not with THC (Vigil et al, 2018;Belendiuk et al, 2015).…”
Section: Sleep Disorders Backgroundmentioning
confidence: 99%
“…66 Observational uncontrolled clinical studies investigating the effects on sleep found CBD (25-300 mg/day) to have positive effects on sleep quality and to decrease sleep disturbances in patients with autism spectrum disorder, 67,68 Parkinson's disease, 69 chronic pain, 70 and in patients with insomnia. 44,71 Again, although the evidence base is of low quality, there is sufficient data to support the hypothesis that CBD would be beneficial in sleep disorders associated with anxiety, which merits testing.…”
Section: Cbd and Sleep Disordersmentioning
confidence: 99%